In Search of the Potentially Hazardous Asteroids in the Taurid Resonant Swarm - Jasmine Li; Quanzhi Ye; Denis Vida; David L. Clark; Eric C. Bellm; Richard Dekany; Matthew J. Graham; Frank J. Masci; Josiah Purdum; Benjamin Racine; Avery Wold (The Planetary Science Journal)
The Taurid Complex is a large interplanetary system that contains comet 2P/Encke, several meteoroid streams, and possibly a number of near-Earth asteroids. The size and nature of the system have led to the speculation that it was formed through a large-scale cometary breakup. Numerical investigations have suggested that planetary dynamics can create a resonant region with a large number of objects concentrated in a small segment of the orbit, known as the Taurid swarm, which approaches the Earth in certain years and provides favorable conditions for studying the Taurid Complex. Recent meteor observations confirmed the existence of the swarm for millimeter- to meter-sized objects. Here we present a dedicated telescopic search for potentially hazardous asteroids and other macroscopic objects in the Taurid swarm using the Zwicky Transient Facility survey. We determine from our nondetection that there are no more than 9–14 H ≤ 24 (equivalent to a diameter of D  ≳ 100 m) objects in the swarm, suggesting that the Encke–Taurid progenitor was  ∼10 km in size. A progenitor of such a size is compatible with the prediction of state-of-the-art solar system dynamical models, which expects  ∼0.1 D  > 10 km objects on Encke-like orbits at any given time.